Clinical profile of acute abdomen cases at a tertiary care hospital - Ravindra, Chimkode; R., Shivakumar C. (International Surgery Journal, 2016)
Background: Abdominal pain is a common presentation in the outpatient setting and is challenging to diagnose. Abdominal pain is the presenting complaint in 1.5 percent of office-based visits1 and in 5 percent of emergency department visits. Methods: All patients with who present with acute abdomen including blunt trauma to abdomen and post-operative cases are included for study and those who give consent for study. A total of 50 cases were studied during the period. Results: Out of 50 cases 37 were due to non-traumatic abdominal pathology and 13 cases were caused by traumatic factor. Conclusions: Abdominal pain is a common presenting complaint in the Emergency Department and clinicians must consider multiple diagnoses, especially in those cases that require immediate intervention in order to limit morbidity and mortality.